The American-Arab Political Relationships: Cooperation or Domination - Bedadda, Roumane, Loubna Bouthaina; Maiassi, Wafa (university of El-Oued, 2020)
The American-Arab relationships are manifested in so many fields such as economic, political, cultural, etc. This research makes an insightful look at the political relationships between Arabs and America. It attempts to reveal some of the strategies and policies that USA adopts in its relations with the Arab world. The research aims to show the real nature of these relations, whether they reflect collaboration or hegemony. The method that has been followed in this research is descriptive-analytical through which a comparison between two variables which are cooperation and domination relationships is held, and analysing some historical events in order to find answers for the research questions and confirm or disconfirm the hypotheses. This research project is very susceptible, and important, because this issue has concerned the public opinion for many decades. ﺗﺘﺠﻠﻰ ﺍﻟﻌﻼﻗﺎﺕ ﺍﻷﻣﺮﻳﻜﻴﺔ ﺍﻟﻌﺮﺑﻴﺔ ﻓﻲ ﺍﻟﻌﺪﻳﺪ ﻣﻦ ﺍﻟﻤﺠﺎﻻﺕ ﻣﺜﻞ: ﺍﻻﻗﺘﺼﺎﺩﻳﺔ ، ﺍﻟﺴﻴﺎﺳﻴﺔ، ﺍﻟﺜﻘﺎﻓﻴﺔ، ﺇﻟﺦ. ﻳﻠﻘﻲ ﻫﺬﺍ ﺍﻟﺒﺤﺚ ﻧﻈﺮﺓ ﺛﺎﻗﺒﺔ ﻋﻠﻰ ﺍﻟﻌﻼﻗﺎﺕ ﺍﻟﺴﻴﺎﺳﻴﺔ ﺑﻴﻦ ﺍﻟﻌﺮﺏ ﻭﺃﻣﺮﻳﻜﺎ، ﻭﺗﺤﺎﻭﻝ ﻫﺬﻩ ﺍﻟﺪﺭﺍﺳﺔ ﺍﻟﻜﺸﻒ ﻋﻦ ﺑﻌﺾ ﺍﻻﺳﺘﺮﺍﺗﻴﺠﻴﺎﺕ ﻭﺍﻟﺴﻴﺎﺳﺎﺕ ﺍﻟﺘﻲ ﺗﺘﺒﻨﺎﻫﺎ ﺍﻟﻮﻻﻳﺎﺕ ﺍﻟﻤﺘﺤﺪﺓ ﻓﻲ ﻋﻼﻗﺎﺗﻬﺎ ﻣﻊ ﺍﻟﻌﺎﻟﻢ ﺍﻟﻌﺮﺑﻲ. ﻭﻳﻬﺪﻑ ﺍﻟﺒﺤﺚ ﺇﻟﻰ ﺎ ﺃﻭ ﻫﻴﻤﻨﺔ. ﺍﻟﻤﻨﻬﺞ ﺍﻟ ﺬﻱ ﺍﺗﺒﻊ ﻓﻲ ﻫﺬﺍ ﺍﻟﺒﺤﺚ ﻫ ﻮ ًﺇﻅﻬﺎﺭ ﺍﻟﻄﺒﻴﻌﺔ ﺍﻟﺤﻘﻴﻘﻴﺔ ﻟﻬﺬﻩ ﺍﻟﻌﻼﻗﺎﺕ ﺳﻮﺍء ﻛﺎﻧﺖ ﺗﻌﺎﻭﻧ ﺗﺤﻠﻴﻠﻲ ﻭﺻﻔﻲ ﺗﺤﺎﻭﻝ ﺍﻟﺪﺭﺍﺳﺔ ﻣﻦ ﺧﻼﻟﻪ ﺍﻟﻤﻘﺎﺭﻧﺔ ﺑﻴﻦ ﻣﺘﻐﻴﺮﻳﻦ ﻭﻫﻤﺎ ﻋﻼﻗﺎﺕ ﺍﻟﺘﻌﺎﻭﻥ ﻭﺍﻟﺴﻴﻄﺮﺓ ﻣﻦ ﺃﺟﻞ ﺍﺳﺘﺨﻼﺹ ﻧﺘﻴﺠﺔ ﻧﻬﺎﺋﻴﺔ، ﻭﻛﺬﻟﻚ ﺇﻳﺠﺎﺩ ﺇﺟﺎﺑﺎﺕ ﻷﺳﺌﻠﺔ ﺍﻟﺒﺤﺚ ﻟﻠﺤﺼﻮﻝ ﻋﻠﻰ ﺍﻟﻨﺘﺎﺋﺞ ﻣﻦ ﺍﻷﻁﺮﻭﺣﺔ ﻭﻣﻌﺮﻓﺔ ﺃﻱ ﺍﻟﻔﺮﺿﻴ ﺘﻴﻦ ﺻﺤﻴﺤﺔ. ﻭﺧﻼﺻﺔ ﺍﻟﻘﻮﻝ ﺇﻥ ﻫﺬﺍ ﺍﻟﺒﺤﺚ ﺣﺴﺎﺱ ﻟﻠﻐﺎﻳﺔ ﻭﻣﻬﻢ ﻷﻥ ﻫﺬﻩ ﺍﻟﻤﺴﺄﻟﺔ ﺗﻤﺲ ﺍﻟﺮﺃﻱ ﺍﻟﻌﺎﻡ ﻟﻌﻘﻮﺩ ﻋﺪﻳﺪﺓ
Keywords: hegemony, political relationships American-Arab, Arab world, collaboration, cooperation and domination; ﺍﻟﺘﻌﺎﻭﻥ، ﺍﻟﺘﻌﺎﻭﻥ ﻭﺍﻟﺴﻴﻄﺮﺓ، ﺍﻟﻌﺎﻟﻢ ﺍﻟﻌﺮﺑﻲ، ﺍﻟﻌﻼﻗﺎﺕ ﺍﻷﻣﺮﻳﻜﻴﺔ ﺍﻟﻌﺮﺑﻴﺔ، ﺍﻟﻌﻼﻗﺎﺕ